2014
DOI: 10.22146/agritech.9457
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK FERMENTATIF MEDIUM deMann Rogosa Sharpe (MRS) ANTOSIANIN BERAS KETAN HITAM (Oryza sativa var. glutinosa) MENGGUNAKAN Pediococcus pentosaceus N11.16

Abstract: Anthocyanin was a bioactive compound which has an anti-infl ammatory effect, anticancer, antimutagen, antioxidant, anticholesterol, and also acts as therapheutic agent for artherioschlerosis. Initial step for anthocyanin metabolism was hydrolyzed to anthocyanidin (aglikon) by β-D-glucosidase. Pediococcus pentosaceus N11.16 is known to be one of bacteria which has a capability to hydrolyze black glutinous rice anthocyanin extract. The aims of this research were to study the fermentative characteristics of MRS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
4
Order By: Relevance
“…The β-glucosidase enzyme is an enzyme that is trapped in the cell wall and has extracellular activity. It is produced by the bacteria L. plantarum Mut 7 (Suhartatik et al, 2013), Pediococcus pentosaceus N11.16 (Suhartatik et al, 2014), a subspecies of Lactobacillus plantarum, Lactobacillus casei LC-01 and L. casei IFPL7190 (Ávila et al, 2009). Table 2 shows that the addition of the inoculum did not significantly affect the anthocyanin levels in white glutinous rice tape.…”
Section: Resultsmentioning
confidence: 99%
“…The β-glucosidase enzyme is an enzyme that is trapped in the cell wall and has extracellular activity. It is produced by the bacteria L. plantarum Mut 7 (Suhartatik et al, 2013), Pediococcus pentosaceus N11.16 (Suhartatik et al, 2014), a subspecies of Lactobacillus plantarum, Lactobacillus casei LC-01 and L. casei IFPL7190 (Ávila et al, 2009). Table 2 shows that the addition of the inoculum did not significantly affect the anthocyanin levels in white glutinous rice tape.…”
Section: Resultsmentioning
confidence: 99%
“…Since the implementation was carried out at different times, differences in the test materials used could affect the results of antioxidant activity. However, Suhartatik et al (2014) showed that the culture of L. plantarum BP102 in MRS broth medium had an antioxidant activity of about 65%. This antioxidant activity occurred due to the presence of phenol compounds in the culture, which was possible from the components of MRS broth which had a phenolic structure, such as amino acids in the beef extract.…”
Section: Antioxidant Activity In Jamu Kunyit Asam During Storagementioning
confidence: 99%
“…Akibatnya, sekresi insulin menurun dan menyebabkan gula darah tinggi. 10 Untuk mencegah penghancuran seluruh sel pankreas, tikus juga disuntik dengan NA, yang dapat melindungi sebagian sel pankreas. 12 Terdapat perbedaan yang signifikan pada kadar GDP kelompok negatif (K-) dan kelompok positif (K+) penyebab rendahnya kadar GDP pada kelompok (K-) dikarenakan pada kelompoknya tidak diinjeksi dengan STZ dan NA.…”
Section: Pembahasanunclassified